Development of Teaching Materials for Physical Fitness Materials Based on AutoPlay Media Studio 8 Application for Students of MTsN 1 Malang City - Barikah, Khasanatul; Kurniawan, Ari Wibowo (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
AutoPlay Media Studio 8 is an interactive multimedia application with many features, this study was developed to facilitate students in understanding physical fitness material. The purpose of this study is to add and develop fitness teaching materials based on AutoPlay Media Studio 8 for students of MTsN 1 Malang City. This type of research is included in research and development. The development model used in this study is ADDIE, which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The sample involved in this study was 60 students of MTsN 1 Malang City. In addition, several experts were involved in product validation, namely 1 physical education learning expert, 1 physical fitness material expert, 1 media expert and 4 practitioners, namely MTsN 1 Malang City PJOK teachers. The instruments used in this study were interview guidelines, product assessment questionnaires, documentation. Based on the data obtained from the results of data analysis by experts, namely learning experts obtained results of 89%, material experts obtained results of 90%, media experts obtained results of 99%, class VII PJOK teacher practitioner experts obtained results of 94%, class VIII PJOK teacher practitioner experts obtained results of 96%, class IX PJOK 1 teacher practitioner experts obtained results of 90%, class IX PJOK 2 teacher practitioner experts obtained results of 83%, class VII field trials 97%, class VIII field trials 98%, class IX field trials 96%. The results of data analysis from experts, practitioners and field trials obtained the results of